Development of Interactive Animation Videos for Civics Learning to Improve the Critical Thinking Abilities of Elementary School Students - Ningsih, Atiya; Udin, Tamsik; Arifuddin, Ahmad; Lubis, Maulana Arafat (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study changed the low critical thinking skills of students caused by students not being accustomed to being trained with indicators in students' critical thinking. To overcome this problem, researchers developed interactive animated video media in Civics learning to improve students' critical thinking skills. This study aims to develop valid and practical interactive animated video media to improve critical thinking skills of grade IV elementary school students. This research uses the Research and Development (R&D) method with the ADDIE model. The data collection techniques used in this study were validation sheets, and practicality questionnaires. The subjects of this study were 23 fourth grade students of Pelandakan 2 State Elementary School in Cirebon City. The results showed a media expert score of 97.22% with the category "very valid", linguists 97.08% with the category "very valid" and material experts 91.39% with the category "very valid". For the practicality of interactive animated video media, the student's practicality score of 90% is categorized as very practical. The trial use of interactive animated videos in Civics learning resulted in a significant increase in critical thinking of grade IV students by obtaining an average N-Gain score of 0.77 with a high classification, so interactive animated video media for Civics learning is effectively used to improve the critical thinking skills of grade IV students in learning.